Content Analysis of Czech School History Textbook with regard to Human Evolution Topics - Dvořáková, Radka Marta; Absolonová, Karolína (Scientia in educatione, 2016)
Our study analysed the factual accuracy of the issue of human evolution as presented in fourteen Czech history textbooks . We focused upon three key ﬁelds — the concept of human evolution, species analysis and the conception of H. sapiens. We point out the fact that the history textbooks contain multiple outdated information and mistakes, such as the linear image of evolution or the persistent labeling of H. neaderthalensis as a subspecies of H. sapiens. We draw attention to some ways in which this misconception is likely to complicate the students’ understanding of evolution in the during subsequent science lessons.